PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWAN DI BANK RAKYAT INDONESIA MAKASSAR CABANG PANAKUKKANG - Vincentia Geralda K. N.; Ratriana Y. E. Kusumiati; Berta Esti Ari Prasetya (Jurnal Cakrawala Ilmiah, 2022)
This study aims to determine the effect between career development on job satisfaction in employees of Bank Rakyat Indonesia Makassar Panakukkang branch. This research uses quantitative methods. The subjects in this study amounted to 31 people, taken using saturated sampling technique where researchers took the entire population of employees as samples. Career development measuring instruments use Veithzal Rivai's theory (2009) while job satisfaction uses Spector's theory (1997). Data collection procedures by distributing questionnaires to employees. The data were processed using Sperman-Rho with the help of SPSS version 25.0. The results showed that R = 49.0% p <0.05 which means that the influence given by career development is 49.0% on job satisfaction and the remaining 61.0% is influenced by other variables that are not in this study. The results obtained from the research conducted are the influence of career development on job satisfaction in employees of Bank Rakyat Indonesia Makassar Panakukkang branch.